Influence of serum leptin levels and Q223R leptin receptor polymorphism on clinical characteristic of patients with rheumatoid arthritis from Western Mexico - Angel-Chávez, Luis Ignacio (2018)
Objective The aim of the present study was to evaluate the possible association between the Q223R Leptin receptor (LEPR) polymorphism (A>G; rs1137101) and leptin levels in patients with rheumatoid arthritis (RA) from Western Mexico. Methods A cross-sectional study was performed with 70 RA patients and 74 controls subject (CS). Disease activity was evaluated using DAS28 score, the Q223R LEPR polymorphism was determined by the Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) and serum leptin levels, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) and rheumatoid factor (RF) were quantified. Results RA patients had significant high serum leptin levels compared with CS; leptin levels correlated strongly with body composition measures, but not with inflammatory markers, disease evolution, and activity. The genotype and allele frequencies of the Q223R LEPR polymorphism were not associated with RA. Similarly, leptin levels did not differ between Q223R LEPR genotypes. Conclusion The LEPR Q223R polymorphism was not associated with RA risk in patients from Mexican population, even though high levels of serum leptin were present and these could explain the low weight observed in RA patients when they were compared to control subjects. However, the serum leptin levels did not correlate with inflammatory markers, severity and disease evolution.